2019
DOI: 10.1002/ajhb.23317
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between total physical activity and physical activity domains with body composition and energy expenditure among Brazilian adults

Abstract: Objective: The aim of this study was to evaluate the relationship of total physical activity (PA) and its different domains with sex, weight, body mass index, body composition, and resting energy expenditure (REE) among Brazilian adults. The secondary aim was to assess if the Baecke Habitual Physical Activity Questionnaire (BHPAQ) could be used to screen fat mass excess. Methods: Three hundred and sixty-six volunteers participated. PA was assessed with the BHPAQ, body composition with multifrequency bioelectri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Given that the equipment for measuring muscle mass, such as DXA, is seldom available in clinical practice, functional evaluations, such as HGS and gait speed tests that are easily applicable are an alternative. This study showed that women are more at risk for muscle impairment, obesity, and sarcopenic obesity, probably related to a more sedentary lifestyle [26], a traditional risk factor for the development of sarcopenia, obesity, and also sarcopenic obesity [6].…”
Section: Discussionmentioning
confidence: 68%
“…Given that the equipment for measuring muscle mass, such as DXA, is seldom available in clinical practice, functional evaluations, such as HGS and gait speed tests that are easily applicable are an alternative. This study showed that women are more at risk for muscle impairment, obesity, and sarcopenic obesity, probably related to a more sedentary lifestyle [26], a traditional risk factor for the development of sarcopenia, obesity, and also sarcopenic obesity [6].…”
Section: Discussionmentioning
confidence: 68%
“…60–62 As discussed above, improved muscle condition may help to improve the pain threshold under mechanical stimulation. 6365 In fact, poor fitness in women with FM is related to increased sensitivity to pain. 66…”
Section: Discussionmentioning
confidence: 99%
“…[60][61][62] As discussed above, improved muscle condition may help to improve the pain threshold under mechanical stimulation. [63][64][65] In fact, poor fitness in women with FM is related to increased sensitivity to pain. 66 Bold type means statistically significant differences between pre-and post-treatment measurements (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…There are no repositories of the BPAQ to identify all the translations, but the questionnaire has been used internationally in different populations with multiple languages, including Japanese , Dutch , Persian , French , Flemish , Greek , Korean , and Portuguese .…”
Section: Baecke Physical Activity Questionnairementioning
confidence: 99%